2014
DOI: 10.1039/c4dt00343h
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous complexation of citrate with neodymium(iii) and americium(iii): a study by potentiometry, absorption spectrophotometry, microcalorimetry, and XAFS

Abstract: The aqueous complexation of Nd(III) and Am(III) with anions of citrate was studied by potentiometry, absorption spectrophotometry, microcalorimetry, and X-ray absorption fine structure (XAFS). Using potentiometric titration data fitting the metal-ligand (L) complexes that were identified for Nd(III) were NdHL, NdL, NdHL2, and NdL2; a review of trivalent metal-citrate complexes is also included. Stability constants for these complexes were calculated from potentiometric and spectrophotometric titrations. Microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 35 publications
(36 reference statements)
1
37
0
Order By: Relevance
“…An isosbestic point observed at 581.3 nm suggested the presence of two absorbing Nd(III) species including Nd(NO3)3. The stability constant of NdL 3+ (L represents NTAamide(C8)) was calculated as 8.27 ± 0.06 [41].…”
Section: Uv-visible Spectra Titration For Nd(iii)/ntaamide(c8)mentioning
confidence: 99%
“…An isosbestic point observed at 581.3 nm suggested the presence of two absorbing Nd(III) species including Nd(NO3)3. The stability constant of NdL 3+ (L represents NTAamide(C8)) was calculated as 8.27 ± 0.06 [41].…”
Section: Uv-visible Spectra Titration For Nd(iii)/ntaamide(c8)mentioning
confidence: 99%
“…The positive entropyo fc oordination for the second uranyl ion can be caused by the release of nitrate ions and hydration water from UO 2 (NO 3 ) 2 ·6H 2 O. [48][49][50] The reorganization of acetonitrile aroundt he complex can also contribute to an increase in the entropy. [48] The entropy value shoulda lso be positive in the complexation of the first uranyl ion.…”
Section: Isothermal Titration Calorimetry (Itc): Determination Of Entmentioning
confidence: 99%
“…A significant number of thermodynamic studies were devoted to the complexation of An(III) or lanthanides (Ln), , with citric acid in various media at various ionic strengths. The outcomes of these studies led to the determination of conditional complexation constants without a precise description of the corresponding complexes.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, only two of them report structure characterizations on the An(III)‐citric acid system, determining the number of water molecules in the primary coordination sphere by time resolved laser‐induced fluorescence spectroscopy (TRLFS) , . In order to supplement the Am system, a number of other studies reported the structural characterizations on the Ln(III) complexes, that can be considered as a analogues of An(III) with close ionic radii . One attempt reports a similar structure characterization of Nd(III) complexes by extended X‐ray absorption fine structure (EXAFS) spectroscopy, the results of which appear to be incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation